Intra-Tumoral Expression of SLC7A11 Is Associated with Immune Microenvironment, Drug Resistance, and Prognosis in Cancers: A Pan-Cancer Analysis - He, Jiajun; Ding, Hongjian; Li, Huaqing; Pan, Zhiyu; Chen, Qian (Frontiers in Genetics, 2021)
Although many anti-cancer modalities have shown potent efficacy in clinical practice, cancer prevention, early detection and effective treatment are still challenging. As a newly recognized iron-dependent cell death mechanism characterized by excessively generation of lipid peroxidation, ferroptosis is regarded as a potent weapon in clearing cancer cells. As the cystine/glutamate antiporter solute carrier family 7 member 11 (SLC7A11) is the core target for ferroptosis regulation, the overexpression of which dictates downregulated sensitivity to ferroptosis in cancer cells. Hence, we elaborated the pan-cancer level bioinformatic study and systematically elucidated the role of intra-tumoral expression of SLC7A11 in the survival of cancer patients and potential immunotherapeutic response. Specifically, 25/27 (92.6%) cancers were featured with upregulated SLC7A11 expression, where SLC7A11 overexpression is a risk factor for worse OS in 8 cancers. We also validated SLC7A11 expression in multiple cancer cell lines in vitro, and found that it was upregulated in most pancreatic cancer cell-lines (P<0.05). Single-cell sequencing method revealed the SLC7A11 was majorly expressed in malignant cells and mononuclear linkages. To further explore the function of SLC7A11 in cancer progression, we analyzed the influence on cell proliferation after the knockdown or knockout of SLC7A11 by either CRISPR or RNAi methods. Besides, the association between SLC7A11 and drug resistance were characterized using bioinformatic approaches as well. We also analyzed the relationship between multi-omics level of SLC7A11 and immune infiltration, the response to immunotherapy, MHC, immune stimulators and inhibitors based on cell annotation tools. In addition, the SLC7A11 expression in COAD, UCEC and STAD is also positively associated with MSI and that in HNSC, STAD and PRAD is positively associated with neoantigen level, which further revealed the potential relationship between SLC7A11 and immunotherapeutic response.